2020
DOI: 10.3390/ijms21197230
|View full text |Cite
|
Sign up to set email alerts
|

Glucose, Fructose, and Urate Transporters in the Choroid Plexus Epithelium

Abstract: The choroid plexus plays a central role in the regulation of the microenvironment of the central nervous system by secreting the majority of the cerebrospinal fluid and controlling its composition, despite that it only represents approximately 1% of the total brain weight. In addition to a variety of transporter and channel proteins for solutes and water, the choroid plexus epithelial cells are equipped with glucose, fructose, and urate transporters that are used as energy sources or antioxidative neuroprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 176 publications
(457 reference statements)
1
29
0
Order By: Relevance
“…Myung et al 3 reported that the choroid plexus is an important circadian clock component, suggesting a great role of the choroid plexus in adjusting circadian rhythm. In addition, it has become well-known that numerous transporters are localized in epithelial cells of the choroid plexus, [36][37][38] indicating more transportation functions of choroid plexus epithelial cells than previously considered those. From these findings, it is likely that choroid plexus dysfunction has significant effects on various brain functions, including cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Myung et al 3 reported that the choroid plexus is an important circadian clock component, suggesting a great role of the choroid plexus in adjusting circadian rhythm. In addition, it has become well-known that numerous transporters are localized in epithelial cells of the choroid plexus, [36][37][38] indicating more transportation functions of choroid plexus epithelial cells than previously considered those. From these findings, it is likely that choroid plexus dysfunction has significant effects on various brain functions, including cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, an isoform of the Na + -coupled glucose transporter (SGLT2; SLC5A2), which was previously annotated to sole expression in the proximal tubules [78], was here detected in the choroidal transcriptome, albeit at a lower relative expression level (6 TPM) than that observed in the proximal tubule sample (22 TPM). The choroidal transcript abundance of SGLT2 is confirmatory of its recently demonstrated protein expression in mouse and human choroid plexus [79, 80]. The proposed selective SGLT2 expression in the proximal tubules led to development of SGLT2 inhibitors as a selective treatment option for type 2 diabetes mellitus [81, 82].…”
Section: Discussionmentioning
confidence: 87%
“…The proposed selective SGLT2 expression in the proximal tubules led to development of SGLT2 inhibitors as a selective treatment option for type 2 diabetes mellitus [81, 82]. Such approach may have to be reconsidered based on SGLT2 expression in choroid plexus (this study and [79, 80]), where the transport protein could potentially partake in CSF secretion, like its homologue, SGLT1, participates in fluid transport across the small intestine [83].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the clearly defined function of URAT1 is to promote reabsorption of uric acid at the apical membrane of proximal tubule epithelial cells (TECs) ( Enomoto et al, 2002 ). GLUT9 functions as a transporter that reabsorbs both uric acid and glucose into tubular cells ( Chiba et al, 2020 ). Accordingly, the regulation of cellular uric acid transporters would be able to result in alteration in urate excretion in the kidney ( Nakayama et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%